PSYCHOLOGICAL AND PEDAGOGICAL ANALYSIS OF THE SOCIALIZATION OF BLIND CHILDREN (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses important tasks for the formation of socially adaptive behavior of visually impaired students in special schools. A new approach to the education and upbringing of blind and visually impaired children will help to successfully solve issues related to learning and skill formation. In modern conditions, the importance of pedagogical expediency in the proper organization of the lifestyle of blind and visually impaired children studying in boarding schools is increasing, which highlights their issues of approximation and integration into the surrounding reality.